2014
DOI: 10.1111/bju.12485
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of coenzyme Q10 in renal injury associated with extracorporeal shockwave lithotripsy: a randomised, placebo‐controlled clinical trial

Abstract: These results are protected by a patent at the Spanish Office of Patents and Trademarks (Reference: P201131992) Objective• To determine the efficacy of coenzyme Q10 (CoQ10) in preventing renal injury in patients with lithiasis undergoing extracorporeal shockwave lithotripsy (ESWL). Patients and Methods• Prospective, randomised, double-blind, placebo-controlled clinical trial of 100 patients with renal lithiasis who were treated with ESWL.• The patients were distributed randomly into two groups receiving either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 37 publications
2
13
0
2
Order By: Relevance
“…Coenzyme Q10, a lipophilic cofactor of the mammalian mitochondrial electron transport chain, is not only crucial for mitochondrial energy production (adenosine 5′‐triphosphate [ATP]), but also has emerged as an effective anti‐oxidant. Coenzyme Q10 has shown some clinical benefits in a number of clinical trials. Huynh et al .…”
Section: Anti‐oxidants In Dcmmentioning
confidence: 99%
See 1 more Smart Citation
“…Coenzyme Q10, a lipophilic cofactor of the mammalian mitochondrial electron transport chain, is not only crucial for mitochondrial energy production (adenosine 5′‐triphosphate [ATP]), but also has emerged as an effective anti‐oxidant. Coenzyme Q10 has shown some clinical benefits in a number of clinical trials. Huynh et al .…”
Section: Anti‐oxidants In Dcmmentioning
confidence: 99%
“…Coenzyme Q10, a lipophilic cofactor of the mammalian mitochondrial electron transport chain, is not only crucial for mitochondrial energy production (adenosine 5 0 -triphosphate [ATP]), but also has emerged as an effective anti-oxidant. Coenzyme Q10 has shown some clinical benefits in a number of clinical trials 67,68 . Huynh et al 69 have treated type 1 diabetic mice at 4 weeks after hyperglycemia that was induced by multiple-low doses of STZ (55 mg/kg/day for 5 days) with coenzyme Q10 or angiotensin-converting-enzyme inhibitor (ACE-I) ramipril for 8 weeks.…”
Section: Coenzyme Q10mentioning
confidence: 99%
“…The endogenous production of coenzyme Q10 declines after the age of 20, and at the age of 80, only half of endogenous production can be found in the heart [40]. Substantial efforts have been done in numerous studies where supplementation of coenzyme Q10 has been evaluated in different conditions, like multiple sclerosis [41,42] , in Parkinson´s disease [43], in patients with renal injury treated with shockwave lithotripsy [44], in male infertility [45], and in heart disease but with inconsistent results [46][47][48]. Fotino et al reported in a meta-analysis consisting of 13 studies and 395 patients increased cardiac function after coenzyme Q10 supplementation even if the total study sample was small [49].…”
Section: Coenzyme Q10mentioning
confidence: 99%
“…He noticed an increased glomerular filtration rate in his study along with a reduction in the concentrations of albumin, creatinine, macroglobulin (β2M) in the coenzyme Q 10 treated group. Further, he concluded CoQ 10 actively involved in maintaining renal function, vasoactive hormonal activities and inflammatory parameters after extracorporeal shockwave lithotripsy 24 .…”
Section: Review Of Literaturesmentioning
confidence: 99%